Police and international peacekeeping missions: securing peace and post-conflict rule of law - Heyer, Garth den; Albrecht, James F. (Springer, 2021)
This edited volume examines the experiences and the roles of the police deployed on peacekeeping and intervention missions in Afghanistan, Bougainville, Cyprus, Haiti, Kosovo, Namibia, Solomon Islands, Timor Leste, and Ukraine. Despite the extensive literature that has examined the role of the military in peacekeeping and intervention operations, little literature or information that investigates the role and the work of the police or the methods that they use to assist in the reformation of local police is available. This book provides an overview of the history and role of the police in peacekeeping missions, and discusses the principle factors of police reform and development in post-conflict nations. It includes case studies assessing the background of the conflict and the police deployments, as well as their role, contributions, and achievements. Including two in-depth surveys of police officer experiences on peacekeeping missions, this volume will be of great value to policing researchers and law enforcement leadership, police historians, and students and researchers of post-conflict development. Examines and critiques approaches to the reform of police organizations in post-conflict nations; Develops detailed case studies of the role of police in international peacekeeping missions and post-conflict assistance; Analyses two extensive surveys of the experiences of police officers deployed to peacekeeping missions